Who Values The Status of The Entrepreneur? - Mirjam van Praag (Tinbergen Institute, 2009)
Parker and Van Praag (2009) showed, based on theory, that the group status of the profession `entrepreneurship' shapes people's occupational preferences and thus their choice behavior. The current study focuses on the determinants and consequences of the group status of a profession, entrepreneurship in particular. If the group status of entrepreneurship is related to individual choice behavior, it is policy relevant to better understand this relationship and the determinants of the status of the entrepreneur. For reasons outlined in the introduction, this study focuses on (800) students in the Netherlands. We find that the status of occupations is mostly determined by the required level of education, the income level to be expected and respect. Furthermore, our results imply that entrepreneurship is associated with hard work, high incomes, but little power and education. Moreover, we find evidence that individual characteristics, such as entrepreneurship experience, vary systematically with the perceived status of occupations, thereby contributing ammunition to a fundamental discussion in the literature. Finally, we find a strong association between the perceived status of the entrepreneur and the estimated likelihood and willingness to become an entrepreneur.
Keywords: J22; J24; L26; M13; M59; 330; Entrepreneurship; self-employment; occupational choice; occupational status; group status; peer group effects; Entrepreneurship-Ansatz; Selbstständige; Berufswahl; Sozialer Status; Wahrnehmung; Soziale Gruppe; Niederlande